Metode riset untuk desain komunikasi visual Jonathan Sarwono, Hary Lubis ; editor, Fl. Sigit Suyantoro - SARWONO, Jonathan; Lubis, Hary; Fl. Suyantoro, Fl. Sigit (Andi, 2007)
xii, 154 hlm. : ilus. ; 23 cm